Awareness, Knowledge and Attitude of Waterpipe Smoking Among University Students in Syria: A Cross Sectional Study - Muaaz Alajlani; Isam Chama; Hiba Mohammad; Raghad Fayyad (University of Mosul, 2024)
Background: Waterpipe smoking, also known as hookah or shisha smoking, has gained popularity in recent years, particularly among young adults and adolescents. Methods: A cross-sectional survey was conducted at four universities in Syria, using an interviewer-administered questionnaire aimed to determine the prevalence of waterpipe smoking among university students in Syria, explore their attitudes and awareness of the health risks, and assess their intentions to quit smoking. 321 students participated in the study with a gender ratio of 44.2% male and 55.8% female. Results: The most common positive perceptions of Waterpipe were related to entertainment (20.6%) and stress reduction (9.3%). The negative perceptions of the waterpipe according to the students, as 29.3% stated that everything in the waterpipe is harmful. Almost every student has stated in a way or another the dangerous and negative effects of smoking waterpipe (99%). A significant percentage of students believe that the most common reasons for using a waterpipe are self-expression, boredom, and the availability of time. The majority of waterpipe smoking students, 83 expressed no plan of giving up smoking (52.8%). Approximately half of the students abstain from smoking waterpipe entirely, attributed to their heightened awareness and understanding of the health hazards associated with smoking, both for themselves and those around them. Only 6.9% of students have named tuberculosis a disease that can be transferred by waterpipe and 36.4% have named influenza virus as waterpipe transferable. Furthermore, 28.7% of participants asserted that the coronavirus is transmitted through waterpipe. Conclusion: Waterpipe smoking poses a significant health challenge in Syria, therefore, this study contributes with data that support eradication of this health issue.